Meningkatkan Hasil Belajar Siswa pada Materi Konsep Pecahan Sederhana Menggunakan Media Puzzle Pecahan Kelas III SDN 2 Setiamulya - Marifah, Nunung; Fatimah Zahrah, Riza; Dwi Febriani, Winarti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The background to this research is the low learning outcomes of students in mathematics lessons in class III at SDN 2 Setiamulya. The aim of this research is to improve students' mathematics learning outcomes by using fraction puzzle media in grade 3 elementary schools in Tasikmalaya. The research method used is Classroom Action Research according to the Kemmis and Mc model. Taggart which consists of planning, action, observation, reflection in each cycle. The subjects in this research were 10 male students and 12 female students. The results of this research state that learning mathematics using fraction puzzle media can improve student learning outcomes. Based on the results of pre-cycle research, cycle I, cycle II, pre-cycle students' learning completeness obtained an average of 40 with a percentage of 31.82% in the very low category and experienced an increase in cycle I, obtaining an average score of 65.18 with a percentage of 59.05%. the poor category then in cycle II obtained an average score of 86.36 with a percentage of 95.45% in the very good category.